Role of Professional Societies on Increasing Indigenous Peoples’ Participation and Leadership in STEMM - Ingram, Jani C.; Castagno, Angelina E.; Camplain, Ricky; Blackhorse, Davona (Frontiers in Education, 2021)
Indigenous people are the most underrepresented racial/ethnic group in Science, Technology, Engineering, Mathematics, and Medicine (STEMM) in the United States. Most prior research suggests this trend is the result broadly of settler colonialism, and more specifically of cultural differences between students and school/university environments; poor academic preparation in K-12 schools; vague constructs of educational or vocational goals; insufficient financial aid; unwelcoming school and university environments; prejudice and racism; and social isolation. There is also a vast body of published work on the unique epistemologies and knowledge systems held by Indigenous peoples, which are only recently being acknowledged within mainstream STEMM communities. One potential reason for lower participation in STEMM programs and professions by Indigenous people that has generally gone unexplored relates to unique cultural and spiritual factors that could deter Indigenous people from STEMM fields. Our research investigates the range and variation of cultural/spiritual/ethical practical issues that may be affecting Indigenous people’s success in STEMM. Our research provides valuable insights for policy and practices within higher education institutions and industry to provide flexible pathways for Indigenous people to reduce or eliminate barriers related to culturally- and spiritually-informed issues. In this paper, we explore how our findings can be used by professional societies to provide leadership to higher education institutions and industry in the area of changing some standard practices to be more inclusive of Indigenous people. An important mode of systemic change in STEMM fields is through professional societies that guide future practices in various STEMM disciplines.